Legal Consequences of Nominee Agreements Due to the Death of the Beneficial According to Statutory Regulations - Rambe, Zahra Khairunnisa; Budhiawan, Adlin (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the legal consequences of nominee agreements when the heir passes away, an issue that remains ambiguous under Indonesian civil law. The research problem arises from the tension between the principle of freedom of contract and the prohibition of legal circumvention through nominee arrangements, particularly in relation to land ownership by foreign nationals. Unlike previous studies that primarily focused on the validity or enforceability of nominee agreements, this research introduces a novel perspective by systematically analyzing the legal implications of termination due to death within the framework of inheritance law and contract annulment. Employing a normative juridical method, the study explores statutory provisions, legal doctrines, and relevant court decisions. The findings indicate that nominee agreements, although often satisfying the formal elements of a contract, frequently contravene the principles of lawful cause and good faith, thereby rendering them void ab initio. Upon the death of the heir, neither the heir nor their successors retain enforceable rights, while the nominee remains the de jure owner. This situation creates legal uncertainty and inheritance disputes. The study concludes that such agreements fail to provide legal protection and instead burden the judiciary with disputes that undermine legal certainty. These findings underscore the necessity for harmonization and reform of Indonesian civil law to ensure certainty, justice, and alignment with contemporary business practices.